2022
DOI: 10.1002/open.202200140
|View full text |Cite
|
Sign up to set email alerts
|

The Global Polarity of Alcoholic Solvents and Water – Importance of the Collectively Acting Factors Density, Refractive Index and Hydrogen Bonding Forces

Abstract: The DHBD quantity represents the hydroxyl group density of alcoholic solvents or water. DHBD is purely physically defined by the product of molar concentration of the solvent (N) and the factor Σn=n×f which reflects the number n and position (f‐factor) of the alcoholic OH groups per molecule. Whether the hydroxyl group is either primary, secondary or tertiary is taken into account by f. Σn is clearly linearly correlated with the physical density or the refractive index of the alcohol derivative. Relationships … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(44 citation statements)
references
References 134 publications
4
25
0
Order By: Relevance
“…Similar correlations of solvent‐dependent infrared frequency shifts with respect to the hydroxyl group density of alcohols are reported by Zhang [7] . The linear correlation of E T (30) as a function of N of the surrounding solvent is physically reasoned due to the energy level of the ground state of B30 is mainly influenced by solvents compared to the excited state [1b,c] . It was also shown that the E T (30) parameter of various alcohols, including monohydric and polyhydric alcohols, correlates significantly with D HBD [1c] .…”
Section: Introductionmentioning
confidence: 98%
See 4 more Smart Citations
“…Similar correlations of solvent‐dependent infrared frequency shifts with respect to the hydroxyl group density of alcohols are reported by Zhang [7] . The linear correlation of E T (30) as a function of N of the surrounding solvent is physically reasoned due to the energy level of the ground state of B30 is mainly influenced by solvents compared to the excited state [1b,c] . It was also shown that the E T (30) parameter of various alcohols, including monohydric and polyhydric alcohols, correlates significantly with D HBD [1c] .…”
Section: Introductionmentioning
confidence: 98%
“…The linear correlation of E T (30) as a function of N of the surrounding solvent is physically reasoned due to the energy level of the ground state of B30 is mainly influenced by solvents compared to the excited state [1b,c] . It was also shown that the E T (30) parameter of various alcohols, including monohydric and polyhydric alcohols, correlates significantly with D HBD [1c] . Furthermore, both the solvent dependent 129 Xe NMR shift and the rate constant k 1 of S N 1 solvolysis reaction of 2‐chloro‐2‐methylpropane ( tertiary butyl chloride) partially correlate with D HBD [1b] …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations